Internalization of Morals Form The Character Of Muslim Islamic Entrepreneurship in The Era of Society 5.0 - Imamul Muttaqin, Muhammad; Suzaki Rifa’i, Ahmad; Nur Rosyidah , Amiliya; Ayyuhda Prisma , Atta; Kanitatun, Siti; Maskanah, Ulfa (Mudir : Jurnal Manajemen Pendidikan, 2023)
In the era of Society 5.0, the character of Islamic entrepreneurship must be formed by internalizing morals in business. To form a good Islamic entrepreneurship character, the internalization of morals in business must be properly implemented. This includes the use of good business ethics and morals, such as honesty, integrity, and social responsibility. In addition, the character of Islamic entrepreneurship must also be built with good religious values, such as maintaining faith and piety and practicing Islamic teachings in business. In the era of Society 5.0, where technology is growing rapidly, Islamic entrepreneurship must also take advantage of existing technology to develop business in a good and ethical way. However, the use of technology must also be balanced with good business ethics and morals so that the character of Islamic entrepreneurship is maintained. To achieve business success, the character of Islamic entrepreneurship must also be formed with a positive attitude, such as self-confidence, perseverance, and creativity. By implementing moral internalization in business and forming a good Islamic entrepreneurial character, it is hoped that entrepreneurs can achieve success in business by upholding good moral and religious values.